2009
DOI: 10.1007/978-1-59745-521-3_23
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Human Cell Lines Lacking Mitochondrial DNA

Abstract: Mitochondria have their own genome, and mitochondrial DNA (mtDNA) encodes 2 ribosomal RNAs, 22 transfer RNAs, and 13 polypeptides that function in oxidative phosphorylation (OXPHOS). mtDNA mutations lead to dysfunction of OXPHOS, resulting in cell death and/or compromised cellular activity. Cell lines lacking mtDNA (termed rho(0) cells) are very effective tools for studying the consequences of mtDNA mutations. rho(0)cell lines have been used widely to investigate relationships between mtDNA mutation, mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(100 citation statements)
references
References 24 publications
5
95
0
Order By: Relevance
“…28 We confirmed that these cells had lost mitochondria by measuring cellular mitochondrial DNA content by quantitative PCR, western blotting cell lysates for the mitochondrial protein ATPase inhibitory factor 1 (ATPIF1), and flow cytometry of cells stained with the mitochondrial specific dye MitoTracker Green ( Fig. 4C and D).…”
Section: Mitochondrial Reactive Oxygen Activates the Inflammasome Folmentioning
confidence: 55%
See 1 more Smart Citation
“…28 We confirmed that these cells had lost mitochondria by measuring cellular mitochondrial DNA content by quantitative PCR, western blotting cell lysates for the mitochondrial protein ATPase inhibitory factor 1 (ATPIF1), and flow cytometry of cells stained with the mitochondrial specific dye MitoTracker Green ( Fig. 4C and D).…”
Section: Mitochondrial Reactive Oxygen Activates the Inflammasome Folmentioning
confidence: 55%
“…Ethidium bromide (500 ng/ml) was added to the medium for 15 d. 28 Depletion of mitochondrial DNA was evaluated by quantitative PCR for the mitochondrial gene mt-Co1, compared to nuclear DNA encoding 18S rRNA, protein gel blot to detect mitochondrial ATPIF1, and flow cytometry for measurement of mitochondrial mass using MitoTracker Green FM stain (Invitrogen, M7514).…”
Section: Protein Transfectionmentioning
confidence: 99%
“…Because avocatin B is a lipid and leukemia cells possess mitochondrial and metabolic alterations that result in their dependence on fatty acid substrates for survival (2), we hypothesized that avocatin B's toxicity was related to its localization in mitochondria. To first test avocatin B's reliance on mitochondria for cytotoxicity, we generated leukemia cells lacking functional mitochondria by culturing Jurkat-T cells in media supplemented with 50 ng/mL of ethidium bromide, 100 mg/mL sodium pyruvate, and 50 mg/mL uridine, as previously described (30,31). Following 60 days of passaging only live cells, the presence of mitochondria were tested by flow cytometry following 10-nonyl acridine orange (NAO) staining and by Western blotting for mitochondrial specific proteins ND1 and adenine nucleotide translocator (ANT).…”
Section: Mitochondria and Cpt1 Are Functionally Important For Avocatimentioning
confidence: 99%
“…HepG2 cells lacking mitochondrial DNA ( 0 cells) were generated by chronic exposure to low doses of ethidium bromide, as described by Hashiguchi and Zhang-Akiyama (34). 0 mitochondria can maintain electrochemical potential across the inner membrane by a mechanism coupled to ATP hydrolysis, making them net consumers of ATP in cells and an excellent tool for studying mitochondrial function (34). The cells were immediately expanded and frozen after being obtained and restarted every 3-4 months from a frozen vial of the same batch of cells, and no additional authentication was done on these cells.…”
Section: Cell Culturementioning
confidence: 99%